Characterizing Photosynthetic Biofuel Production: Isotopically Non-Stationary 13C Metabolic Flux Analysis on Limonene Producing Synechococcus sp. PCC 7002 - Newman, Darrian M.; Sake, Cara L.; Metcalf, Alexander J.; Davies, Fiona K.; Cano, Melissa; Krishnan, Anagha; Boyle, Nanette R. (Frontiers in Energy Research, 2022)
Synechococcus sp. PCC 7002 is a unicellular cyanobacterium capable of fast growth, even under high light intensity and high salinity. These attributes along with genetic tractability make Synechococcus sp. PCC 7002 an attractive candidate for industrial scale production of specialty and commodity chemicals. One such strain produces limonene, an energy dense diesel jet fuel drop-in additive, at a titer of 4 mg/L over a four-day incubation period. In this study, we use the state-of-the-art whole-cell characterization tool, isotopically non-stationary 13C metabolic flux analysis (INST-13CMFA) to determine intracellular fluxes through the pathways of central metabolism for the limonene producing strain and wild type strain of Synechococcus sp. PCC 7002. We find similar flux distribution in the Calvin-Benson-Bassham cycle, photorespiration, oxidative pentose phosphate pathway, and reductive tricarboxylic acid cycle. The key difference between strains is observed in the production of pyruvate. The limonene producing strain displays significantly higher flux through the amphibolic pathways of phosphoenolpyruvate carboxylase and the malic enzyme to synthesize pyruvate, while the wild type strain uses pyruvate kinase in a single step. Our findings suggest that this flux distribution is a mechanism to recover a physiologically optimal ratio of ATP to NADPH. The upregulation of this amphibolic pathway may act to restore the physiological ATP:NADPH ratio that has been disturbed by limonene biosynthesis.